Parenteral Iron Sucrose Therapy for Moderate and Severe Iron-De?ciency Anemia in Pregnancy - Kamlesh; Singh, Mahender; Kaur, Mandeep; Sapehia, Varsha (Asian Journal of Medical Research, 2021)
Introduction: In India, women become pregnant with low baseline hemoglobin levels resulting in high incidence of moderate to severe anemia in pregnancy where oral iron therapy cannot meet the requirement. Pregnant women with moderate to severe anemia are to be treated with parenteral iron therapy. This study was done to evaluate the effect and response of intravenous iron sucrose given to pregnant women with iron deiciency anemia (IDA). Subjects and Methods: A prospective observational study was conducted in 60 pregnant women with documented IDA with Hb between 6-9 gms % were given intravenous iron sucrose 200 mg thrice weekly after calculating the dose requirement. Analysis of data was done by using paired T test. Results: The mean Hb raised from7.82 0.93 to 10.8 1.2 after 8 weeks of therapy. There was signiicant increase in serum ferritin levels from12.4 0.54 to 66.35 18.5. Other parameters including hematocrit, serum iron, TIBC were also improved signiicantly. No major anaphylactic reactions were observed during the study period. Conclusion: Intravenous iron sucrose therapy was effective in increasing Hb, S.Ferritin and other hematological parameters in pregnant women with moderate anemia.